Blood Circuits: Contemporary Argentine Horror Cinema - Risner, Jonathan (SUNY Series in Latin American Cinema Series, 2018)
Examines how recent Argentine horror films engage with the legacies of dictatorship and neoliberalism.
https://katalog.adlr.link/Record/76-EBC5473311